Sugarcane Fertilization Innovation: Enhancing Productivity and Sustainability in the Philippines - Yuan, Bro. Jian Meng; Oñal, Jr., Paulino A.; Oñal, Paulino Miguel M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Economically, the sugarcane industry is one of the major sources of dollar income in the Philippines.  It is planted in different types of soil, environments, and cultural management. Sugarcane is a voracious eater of fertilizer. The main purpose of innovating the fertilization activities in the farm is to increase production in order to sustain the sugarcane industry. The study aims to measure the fertilization innovations practice by the farmers that could affect the production of the sugarcane crop in the Philippines. The descriptive method was employed in the study. The instrument used was the validated survey questionnaire used by the group of Oñal in their study in 2021. The 320 sugarcane farmers were randomly identified at the seven locations in the Visayas area of the Philippines. Analysis of variance (ANOVA) implied that there’s a significant difference in the production of sugarcane among the different locations in the Philippines. Furthermore, the frequency of applying the fertilizers, the correct placement of fertilizers, maximizing the application of N and K elements, and the combo application of organic-inorganic fertilizers implied a high production respectively.  The correct placement of fertilizers and the application of organic-inorganic fertilizers were strongly correlated with sugarcane production but moderately correlated with the level of N and P elements applied. The study revealed that fertilization innovations had a significant relationship in increasing the productivity of the sugarcane crop in the Philippines.